K-water's Integrated Water Resources Management system (K-HIT, K-water Hydro Intelligent Toolkit). Issue 6 (17th August 2020) - Yi, Sukuk; Ryu, Munhyun; Suh, Jinsuhk; Kim, Shangmoon; Seo, Seokkyu; Kim, Seonghan; Jang, Sungphil
ABSTRACT: This study details the Hydro Intelligent Toolkit (K-HIT) developed in 2002 by K-water, the Korean water agency, to cope with extreme events such as floods and droughts. It is structured to outline the challenges to water management in Korea, the development and components of K-HIT, its effectiveness in practice, and lessons learned.